Pays Baltes – Russie. L’impossible coopération transfrontalière ? - Yann Richard (L'Espace Politique)
The European Union has put into place a series of instruments and regulations in order to enhance the cooperation between border regions. This initiative contributes to the European integration and to the construction of the Common European Space. The European instruments and regulations are not only implemented along the internal borders, i.e. between the border countries, but also along the external borders, i.e. between member and third countries. In this paper, we draw the balance sheet of the territorial cross border cooperation between Russia and the Baltic countries. In this part of Europe, cross border cooperation suffers serious setbacks. No projects have been launched between 2007 and 2010, although European cooperation instruments were deeply reformed. The causes of such a failure lie inside and outside EU. Besides, the European Union has not managed to build instruments that could be easily used by project partners and political authorities in third countries. And what was initially presented by the European Commission as a purely technical cooperation programme is seriously hampered by deep political disagreements and tensions between States, and by a lack of vision in the EU. It seems that priority is given to security more than to cooperation by top political stakeholders.